Coleoptera diversity and soil properties in land use systems - Pompeo P.N.* (2020)
© 2020 Universidade Federal Rural do Rio de Janeiro (UFRRJ).This study aimed to evaluate the abundance and diversity of Coleoptera in five land use systems (LUS) and the soil properties that explain the distribution of these organisms. Uses involved native forest (NF), Eucalyptus plantation (EP), perennial pasture (PA), integrated crop-livestock (ICL) and no-tillage (NT) in western Santa Catarina, Brazil. Coleopterans were sampled by the methods of pitfall traps and soil monoliths during the winter and summer. Regardless of the LUS, 1,441 individuals were captured, with Staphylinidae being the most representative family (~47%). The use of NF showed higher abundances of coleopterans. The land use systems PA, NT, and ICL obtained high values of diversity of Coleoptera families, depending on the method and season of collection. The distribution of families was influenced by the sampling season, and some soil properties such as biopores, water content and phosphorus can explain the variation of abundance among the LUS.